Cytokine profile characterization of naïve patients with psoriasis and psoriatic arthritis: implications for a pathogenic disease continuum - Ruscitti, Piero; Esposito, Maria; Di Cola, Ilenia; Pellegrini, Cristina; De Berardinis, Andrea; Mastrangelo, Mirco; Gianneramo, Camilla; Barile, Antonio; Fargnoli, Maria Concetta; Cipriani, Paola (Frontiers in Immunology, 2023)
-Background The idea of psoriatic disease continuum has been progressively prompted based on the advances of the knowledge about the pathogenic steps underpinning the occurrence of psoriasis (PSO) and psoriatic arthritis (PSA). To evaluate biomolecules (inflammatory cytokines, inflammatory chemokines, cell adhesion and cellular mediators) in naïve patients with PSO, PSA with PSO, and PSA sine PSO. To stratify the results considering the presence of psoriatic nail involvement, extensive skin disease and obesity evaluating all involved patients. -Methods By multiplex technology, 20 serum biomolecules were assessed with the inclusion of pro-inflammatory cytokines (GM-CSF, IFN-γ, IL-1, IL-1, IL-6, IL-8, IL-12p70, IL-17A, IL-23, TNF), anti-inflammatory cytokines (IFN-, IL-4, IL-10, IL-13), inflammatory chemokines (IP-10, MCP-1, MIP-1, MIP-1), cell adhesion and cellular mediators (ICAM-1, E-selectin, P-selectin). The assessment of possible statistical differences between the means of the three groups was performed by One-Way ANOVA. In addition, by non-parametric T-tests, we stratified the results according to selected clinical characteristics (psoriatic nail involvement, PASI ≥ 10, BMI ≥ 30). -Results In 80 assessed naïve patients, patients with PSO showed significant increases of E-selectin (p=0.021) and IL-8 (0.041) than other groups. In patients with PSA with PSO, significant higher levels of ICAM-1 were observed (p=0.009) than other groups. We did not observe further differences comparing pro-inflammatory and anti-inflammatory cytokines, inflammatory chemokines, and cell adhesion and cellular mediators in patients with PSO, PSA with PSO, and PSA sine PSO. Patients with psoriatic onychopathy showed significant increased levels of ICAM-1 (p=0.010) and IP-10 (0.030) than others. In patients with PASI ≥ 10, significantly enhanced values of IL-8 (p=0.004), TNF (p=0.013), E-selectin (p=0.004), MIP-1α (p=0.003), and MIP-1β (p=0.039). In patients with BMI ≥ 30, significantly higher levels of E-selectin were pointed out (p=0.035) than others. -Conclusions Our findings may suggest that a similar cytokine profile may characterize naïve patients with PSO, PSA with PSO, and PSA sine PSO, reinforcing the concept of psoriatic disease continuum. However, some differences may be also shown, underlying possible pathogenic differences and leading to the clinical heterogeneity of these patients.